Improving Energy Efficiency in Iasi, Romania - Mot, Manuela; Bose, Ranjan; Burduja, Sebastian; Ionescu-Heroiu, Marcel (World Bank, Washington, DC, 2016)
The Tool for Rapid Assessment of City Energy (TRACE) is used for conducting rapid assessments of energy use in cities. It helps prioritize sectors with significant energy savings potential, and identifies appropriate energy efficiency interventions across six sectors-transport, municipal buildings, water and waste water, public lighting, solid waste, and power and heat. It is a simple, low-cost, user-friendly, and practical tool that can be applied in any socioeconomic setting. This report is based on the implementation of the TRACE tool in Iasi in July 2013 and it outlines ideas on what the city could further do to improve its energy efficiency performance. It details the analysis carried out and the recommendations derived as a result, for energy efficiency action plan and strategy, district heating maintenance and upgrade, non-motorized transport, public transport development, traffic flow optimization, parking restraint measures, municipal building benchmarking program, traffic restraint measures, municipal buildings audit and retrofit, and street lighting timing program.